Analisis Kestabilan Emosi Mahasiswa Yang Berlatar Belakang Keluarga Broken Home: Penelitian - Anisya Tiara Shafiira; Fatma Nofriza (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This study aims to analyze the emotional stability of student with broken home family background. This research uses qualitative research methods with a case study approach and data collection techniques are carried out through observation, interviews, and documentation techniques. The research subjects amounted to 2 students, and this research was conducted at Seruni Hills housing, Bekasi. The result showed that two students from broken home families, FB and DN tend to experience emotional instability characterized by frequent feelings of anxiety , anger, and loneliness, when faced with various Conflicts that come. Although the subjects have carried out various coping strategies, at the time of the research, they were still unable to fully overcome the emotional instability they felt.